Differentiating among incretin-based therapies in the management of patients with type 2 diabetes mellitus - Cobble Michael (Diabetology & Metabolic Syndrome, 2012)
Abstract The glucagon-like peptide-1 receptor (GLP-1R) agonists and dipeptidyl peptidase-4 (DPP-4) inhibitors have become important options for the management of patients with type 2 diabetes mellitus. While the GLP-1R agonists and DPP-4 inhibitors act on the incretin system to regulate glucose homeostasis, there are important clinical differences among the five agents currently available in the U.S. For example, the GLP-1R agonists require subcutaneous administration, produce pharmacological levels of GLP-1 activity, promote weight loss, have a more robust glucose-lowering effect, and have a higher incidence of adverse gastrointestinal effects. In contrast, the DPP-4 inhibitors are taken orally, increase the half-life of endogenous GLP-1, are weight neutral, and are more commonly associated with nasopharyngitis. Differences in efficacy, safety, tolerability, and cost among the incretin-based therapies are important to consider in the primary care management of patients with type 2 diabetes mellitus.